2018
DOI: 10.7554/elife.42849
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels and neuropathic pain

Abstract: Pain behaviors in a Fabry mouse model are associated with the accumulation of a fat molecule that disrupts sodium ion channels in small fiber neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…6 Even though other ion channels might also be involved, this demonstrated that increased amounts of Gb3 can lead to pathological, physiological, and behavioral signs of neuropathy. 109 Neuron hyperexcitability in DRGs soma has been analyzed in relation to Na v channels. Local anesthetics, block pain via nonselective inhibition of Nav channels in primary afferent nerve fibers of the somatosensory nervous system.…”
Section: Ion Channels and Pain In Fdmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Even though other ion channels might also be involved, this demonstrated that increased amounts of Gb3 can lead to pathological, physiological, and behavioral signs of neuropathy. 109 Neuron hyperexcitability in DRGs soma has been analyzed in relation to Na v channels. Local anesthetics, block pain via nonselective inhibition of Nav channels in primary afferent nerve fibers of the somatosensory nervous system.…”
Section: Ion Channels and Pain In Fdmentioning
confidence: 99%
“…6 Even though other ion channels might also be involved, this demonstrated that increased amounts of Gb3 can lead to pathological, physiological, and behavioral signs of neuropathy. 109…”
Section: Ion Channels and Pain In Fdmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs), ion channels, and lncRNAs are critical in the transmission and modulation of nociceptive information ( Zhao et al, 2013 ; Campbell and Smrcka, 2018 ; Klein and Oaklander, 2018 ). Besides 7–8% of the whole transcriptome that are lncRNAs, about 617, 552, and 598 DEGs were identified as GPCR mRNAs and 257, 253, and 250 DEGs were identified as ion channel mRNAs in the SC, ACC, and AMY, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…17,20 Considering hyperexcitability is a hallmark of pain, epilepsy, and anxiety disorders, potassium channels may provide a molecular target to influence neuronal excitability. 39,40 Various plasma membrane and intracellular potassium channels could be pharmacologically targeted to treat pain diseases, [41][42][43][44] such as Piezo2, Nav1.8 and TACAN. 45,46 Kv1.1 channel controls the excitability of neuronal cells.…”
Section: Discussionmentioning
confidence: 99%